Training on Using Prezi as an Innovative Learning Media - Nursaid Nursaid; M Hafrison; Marlini Marlini; Ayu Gustia Ningsih; Vivi Indriyani; Kurniawan Kurniawan (Universitas Lancang Kuning, 2023)
The skills of using Information and Communication Technology (ICT) by teachers have a significant influence on the teacher's ability to use appropriate learning media, which is a key factor in the success of the teaching process. Therefore, SMP Negeri 1 Mungka Regency has designed learning that is suitable for the situation after the COVID-19 pandemic. The purpose of this service project is to provide knowledge and training to teachers of SMP N 1, Mungka District, Fifty Cities Regency in using Prezi-based technology as a learning medium. The training begins with an explanation of the relationship between media and learning, as well as the role of the media in the learning process in the post-COVID-19 pandemic era. Then, the training materials cover how to create a Prezi account, how to register for Prezi, how to install, and how to use it in learning. The training method involved questions and answers, hands-on practice, and demonstrations, and evaluation was carried out through distribution of questionnaires before and after the training. The results of the questionnaire analysis showed that in general the participants were satisfied with the schedule and time of the training, as well as with the topics presented. Although some participants experienced difficulties due to inadequate internet connection and devices, there were indications that participants had succeeded in increasing their knowledge and motivation in terms of using Prezi technology as a learning medium. In addition, the simple works of the participants were also considered quite good.